2020
DOI: 10.1097/mao.0000000000002763
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Otosclerosis: A Population-based Study of Disease Incidence Spanning 70 Years

Abstract: Objective: Although it is commonly held that otosclerosis has become increasingly uncommon over recent decades, no population-based data exist to characterize this trend. Moreover, because most large epidemiologic databases within the United States primarily include cancer data, even the modern incidence of otosclerosis is unknown. The chief objective of the current work was to characterize the trend in the incidence of otosclerosis over 70 years using the unique resources of the Rochester Epidemiology Project. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…For instance, in a recent incidence study of otosclerosis in the same population as the current study, the incidence rates of otosclerosis per 100,000 person-years in the first 3 years of the study (1970)(1971)(1972) were 24.6 in women and 13.6 in men. 15 By contrast, in the most recent 3 years (2015-2017), the incidence rates of otosclerosis were 3.2 in women and 3.1 in men. 15 These trends suggest that the differences in incidence rates between women and men have all but disappeared over the past 45 years.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, in a recent incidence study of otosclerosis in the same population as the current study, the incidence rates of otosclerosis per 100,000 person-years in the first 3 years of the study (1970)(1971)(1972) were 24.6 in women and 13.6 in men. 15 By contrast, in the most recent 3 years (2015-2017), the incidence rates of otosclerosis were 3.2 in women and 3.1 in men. 15 These trends suggest that the differences in incidence rates between women and men have all but disappeared over the past 45 years.…”
Section: Discussionmentioning
confidence: 94%
“…Otosclerosis symptoms appear between age 30 and 50 years. 1 , 2 , 6 , 21 Between 13% and 58% of cases are hereditary. 1 , 21 Otosclerosis surgery has a reported success rate of more than 90%.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, a recent population-based study showed that the incidence of surgically confirmed otosclerosis declined from 12.9 cases per 100,000 person-years in the early 1970s to just 2.1 per 100,000 from 2015 to 2017. 3…”
mentioning
confidence: 99%
“…To this end, a recent population-based study showed that the incidence of surgically confirmed otosclerosis declined from 12.9 cases per 100,000 person-years in the early 1970s to just 2.1 per 100,000 from 2015 to 2017. 3 Applying the age-and sex-standardized incidence rates of surgically confirmed otosclerosis to the 2010 US census data, residents' realistic case exposure to stapedectomy exposure throughout residency can be approximated. 3,4 Inclusion of reported survey data regarding the proportion of private practice otolaryngologists performing stapedectomy and surgeon comfort level with resident participation in this procedure also allows for more accurate estimation of individual resident experience with stapedectomies during training.…”
mentioning
confidence: 99%
See 1 more Smart Citation